Spatial analysis of Measles risk areas in Bantul District of Yogyakarta Province - Rosa Devitha Ayu; Agung Nugroho; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Spatial analysis of measles risk areas in Bantul District of Yogyakarta Province in 2014 PurposeThe purpose of this study was to determine the area of measles risk.MethodsThis research used a cross-sectional design and was performed from June to August 2015. The data on measles patients were obtained from Case-Based Measles Surveillance (CBMS) activities in Health Office of Bantul District. The coordinate locations of patients’ homes were obtained by direct visits. Meanwhile, the information regarding village/ward areas was derived from all village/ ward offices and Public Health Centers in Bantul Districts. The data were analyzed by spatially weighted regression tests.ResultsThere were 185 measles cases and 6 outbreaks spread-out in 50 (67%) villages/wards. The entire villages/wards have achieved immunization coverage of >90%, 66% with good nutritional status, 51% with high education status, 37% with high population density, and 24% with low economic status. The variable of population density was spatially associated with measles incidents while immunization coverage, nutritional status, education level, and economic status were not spatially associated with measles incidents. Measles case clustering was found in the areas of Banguntapan Sub-district.ConclusionThe immunization program in Bantul District should be evaluated in the light that the villages/wards have achieved immunization coverage of 90% but 185 measles cases and 6 outbreaks were still found in 2014. In addition, the improvement of the immunization recording system needs be conducted for CBMS activities.